2014
DOI: 10.3856/vol42-issue5-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluacion de la tasa de consumo de oxigeno de Colossoma macropomum en relacion al peso corporal y temperatura del agua

Abstract: Evaluación de la tasa de consumo de oxígeno de (5x3x3), utilizando un respirómetro de 20 L y una bomba de recirculación de agua. Las mediciones del CO fueron realizadas cada 5 min mediante el uso de un oxímetro digital. Los resultados indican que el CO mantiene relación directa con la temperatura del agua e inversa con el peso corporal de los organismos (P < 0,05). Las regresiones entre las variables independientes y el CO se ajustaron a ecuaciones potenciales: CO = 2844,9 P -0,734, CO = 2555,9 P -0,624 y CO =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
2
Order By: Relevance
“…The temperature variable oscillated below the optimal value of 28ºC (Azaza et al 2008), without presenting significant differences between the treatments during the three stages of development (juvenile, juvenile, and adult). The dissolved oxygen concentration had a decrease throughout the development stages, being that higher total biomass in the tanks leads to higher oxygen consumption (Valbuena-Villareal et al 2006, Tomalá et al 2014; however, within each development stage (juvenile, juvenile, and adult), the treatments did not show significant differences. So, it can be inferred that the dissolved oxygen did not limit the development of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature variable oscillated below the optimal value of 28ºC (Azaza et al 2008), without presenting significant differences between the treatments during the three stages of development (juvenile, juvenile, and adult). The dissolved oxygen concentration had a decrease throughout the development stages, being that higher total biomass in the tanks leads to higher oxygen consumption (Valbuena-Villareal et al 2006, Tomalá et al 2014; however, within each development stage (juvenile, juvenile, and adult), the treatments did not show significant differences. So, it can be inferred that the dissolved oxygen did not limit the development of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Además, en bajas concentraciones de oxígeno disuelto los peces son más susceptibles a enfermedades, ya que la actividad metabólica se ve limitada (Tomalá, Chavarría y Escobar, 2014). En los lagos, los problemas se agravan al considerar la condición endorreica, ya que la única entrada de agua al sistema es de naturaleza pluvial (por lluvia), mientras que su única salida es por evaporación, lo que le confiere una dinámica de dilución y concentración temporal, aunque ligada al ciclo anual de precipitación (Bernal-Brooks, 2002).…”
Section: Discussionunclassified
“…macropomum [ 61 ]. A study found that individuals with a body weight above 250 g have tolerance to low oxygen concentrations due to high temperatures [ 62 ]. In addition, the ability of C .…”
Section: Discussionmentioning
confidence: 99%